Even Small Decreases in Blood Pressure during Conscious Sedation Affect Clinical Outcome after Stroke Thrombectomy: An Analysis of Hemodynamic Thresholds - Whalin, M.K.; Halenda, K.M.; Haussen, D.C.; Rebello, L.C.; Frankel, M.R.; Gershon, R.Y.; Nogueira, R.G. (American Journal of Neuroradiology, 2017)
BACKGROUND AND PURPOSE: The adverse effects of general anesthesia in stroke thrombectomy have been attributed to intraprocedural hypotension, yet optimal hemodynamic targets remain elusive. Identifying hemodynamic thresholds from patients without exposure to general anesthesia may help separate the effect of hypotension from the effect of anesthesia in thrombectomy outcomes. Therefore, we investigated which hemodynamic parameters and targets best correlate with outcome in patients treated under sedation with monitored anesthesia care.MATERIALS AND METHODS: We performed a retrospective analysis of a prospectively collected data base of patients with anterior circulation stroke who were successfully reperfused (modified TICI ≥ 2b) under monitored anesthesia care sedation from 2010 to 2015. Receiver operating characteristic curves were generated for the lowest mean arterial pressure before reperfusion, both as absolute values and relative changes from baseline. Cutoffs were tested in binary logistic regression models of poor outcome (90-day mRS > 2).RESULTS: Two-hundred fifty-six of 714 patients met the inclusion criteria. In a multivariable model, a ≥10% mean arterial pressure decrease from baseline had an OR for poor outcome of 4.38 (95% CI, 1.53–12.56; P < .01). Other models revealed that any mean pressure of <85 mm Hg before reperfusion had an OR for poor outcome of 2.22 (95% CI, 1.09–4.55; P = .03) and that every 10-mm Hg drop in mean arterial pressure below 100 mm Hg had an OR of 1.28 (95% CI, 1.01–1.62; P = .04).CONCLUSIONS: A ≥10% mean arterial pressure drop from baseline is a strong risk factor for poor outcome in a homogeneous population of patients with stroke undergoing thrombectomy under sedation. This threshold could guide hemodynamic management of patients during sedation and general anesthesia.MACmonitored anesthesia careMAPmean arterial pressure